MANAGEMENT ACCOUNTING FOR A PORTFOLIO OF PROJECTS TO SUPPORT ORGANISATIONAL VALUE MAXIMISATION - Viljoen, P.J. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT:The objective of management accounting is to provide management with the financial information that will enable them to make decisions that will result in increased profitability of their organisation. The management accounting of projects in a portfolio as proposed in the literature often presents major problems that prevent the achievement of this objective. These problems include how to estimate value in financial terms during the pre-project phase of the project life cycle as well as the difficulties with financial control of the portfolio of projects as they are conducted. A few case studies are presented highlighting, current practice and the negative effects being experienced. A simple throughput accounting model for the financial management of a portfolio of projects, that could lead to better management decisions and increased profitability of organisations, is proposed. AFRIKAANSE OPSOMMING: Die doelwit van bestuursrekeningkunde is om bestuur te voorsien met finansi